The Influence of Pancasila Education on Students' Awareness and Understanding of LGBT Issues at Universitas Budi Darma - Hutabarat, Sumiaty Adelina (Literacy: Journal of Education and Social Science, 2025)
This study aims to analyze the influence of Pancasila Education on the awareness and understanding of Universitas Budi Darma students regarding LGBT issues. The research employs a qualitative method with a case study approach and data collection through in-depth interviews with several students from various study programs. The findings indicate that Pancasila Education plays a significant role in shaping tolerant attitudes, critical thinking, and a values-based perspective grounded in Pancasila when interpreting the LGBT social phenomenon. Although there are differing viewpoints among students, the majority of respondents recognize the importance of respecting human rights without neglecting cultural and religious values. These findings contribute to the development of a more responsive Pancasila Education curriculum that addresses contemporary social issues among the younger generation.